Carbon, Nitrogen, and Phosphorus Allocation Strategy Among Organs in Submerged Macrophytes Is Altered by Eutrophication - Rao, Qingyang; Su, Haojie; Deng, Xuwei; Xia, Wulai; Wang, Lantian; Cui, Wenjian; Ruan, Linwei; Chen, Jun; Xie, Ping (Frontiers in Plant Science, 2020)
The allocation of limiting elements among plant organs is an important aspect of the adaptation of plants to their ambient environment. Although eutrophication can extremely alter light and nutrient availability, little is known about nutrient partitioning among organs of submerged macrophytes in response to eutrophication. Here, we analyzed the stoichiometric scaling of carbon (C), nitrogen (N), and phosphorus (P) concentrations among organs (leaf, stem, and root) of 327 individuals of seven common submerged macrophytes (three growth forms), sampled from 26 Yangtze plain lakes whose nutrient levels differed. Scaling exponents of stem nutrients to leaf (or root) nutrients varied among the growth forms. With increasing water total N (WTN) concentration, the scaling exponents of stem C to leaf (or root) C increased from <1 to >1, however, those of stem P to root P showed the opposite trend. These results indicated that, as plant nutrient content increased, plants growing in low WTN concentration accumulated leaf C (or stem P) at a faster rate, whereas those in high WTN concentration showed a faster increase in their stem C (or root P). Additionally, the scaling exponents of stem N to leaf (or root) N and stem P to leaf P were consistently large than 1, but decreased with a greater WTN concentration. This suggested that plants invested more N and P into stem than leaf tissues, with a higher investment of N in stem than root tissues, but eutrophication would decrease the allocation of N and P to stem. Such shifts in plant nutrient allocation strategies from low to high WTN concentration may be attributed to changed light and nutrient availability. In summary, eutrophication would alter nutrient allocation strategies of submerged macrophytes, which may influence their community structures by enhancing the competitive ability of some species in the process of eutrophication.